Development and validation of a TaqMan-MGB real-time RT-PCR assay for simultaneous detection and characterization of infectious bursal disease virus - Tomás, Gonzalo (2012)
Rapid and reliable detection and classification of infectious bursal disease viruses (IBDVs) is of crucial importance for disease surveillance and control. This study presents the development and validation of a real-time RT-PCR assay to detect and discriminate very virulent (vv) from non-vv (classic and variant) IBDV strains. The assay uses two fluorogenic, minor groove-binding (MGB) TaqMan probes targeted to a single nucleotide polymorphism (SNP) embedded in a highly conserved genomic region. The analyti- cal sensitivity of the assay was determined using serial dilutions of in vitro-transcribed RNA. The assay demonstrated a wide dynamic range between 102 and 108 standard RNA copies per reaction. Good repro- ducibility was also detected, with intra- and inter-assay coefficients of variation ranging from 0.13% to 2.23% and 0.26% to 1.92%, respectively. The assay detected successfully all the assessed vv, classical, and variant field and vaccine strains and correctly discriminated all vvIBDV strains from non-vvIBDV strains. Other common avian RNA viruses tested negative, indicating high specificity of the assay. The high sensi- tivity, rapidity, reproducibility, and specificity of the real-time RT-PCR assay make this method suitable for general and genotype-specific detection and quantitation.